Stylar end browning: a physiological disorder of Indian jujube (Ziziphus mauritiana) fruits - KRISHNA, HARE; SHARMA, BRIJESH DUTT; BHARGAVA, RAKESH; SINGH, RAMA SHANKER (The Indian Journal of Agricultural Sciences, 2016)
A physiological disorder has been noted in Indian jujube or ber (Ziziphus mauritiana Lamk.) cv. Chhuhara, wherein tip (stylar end) of the ber fruits turned brown. The disorder has been found to aggravate with the progress in the maturity. The disorder affected fruits had less soluble solids content, reducing and total sugars and ascorbic acid; besides higher content of secondary metabolites and enzymes responsible for oxidative browning. Upon nutrient analyses, the boron content found to be higher in affected fruits in comparison to normal, healthy fruits. Since, this disorder appears during late harvesting period, when atmospheric temperature is higher, it may be concluded that high temperature and evapo-transpiration accompanied with high illumination had resulted in boron accumulation beyond its threshold level, which led to the development of browning of stylar end of fruits in ber cv. Chhuhara.